Lucky stiff - Ryan, Annelise (Ryan, Annelise. Mattie Winston mystery., 2013)
When a paraplegic who recently won a huge casino jackpot dies in a house fire, all bets are off as deputy coroner Mattie Winston and detective Scott Hurley, convinced that he was murdered for his money, take a gamble on the wrong suspect.